Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fvets.2020.579189
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality, Voluntary Intake and Enteric Methane Emissions of Diets Based on Novel Cayman Grass and Its Associations With Two Leucaena Shrub Legumes

Abstract: Methane (CH 4 ) emissions from enteric fermentation in cattle are an important source of greenhouse gases, accounting for about 40% of all agricultural emissions. Diet quality plays a fundamental role in determining the magnitude of CH 4 emissions. Specifically, the inclusion of feeds with high digestibility and nutritional value have been reported to be a viable option for reducing CH 4 emissions and, simultaneously, increase animal productivity. The present study aimed to evaluate the effect of the nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 64 publications
(73 reference statements)
2
32
1
Order By: Relevance
“…Similarly, concentrations of phenolic compounds were lower in the grasses than the legumes. These findings concur with data reported in the literature for these tropical species (Lee, 2018;Cook et al, 2020;Gaviria-Uribe et al, 2020), where CP values for grasses can range between 40 and 140 g kg −1 DM, and for both legumes studied here, shrub and herbaceous, ranged between 190 and 250 g CP kg −1 DM. However, the CP content obtained in the present study was slightly lower than that reported by Peters et al (2002) for U. brizantha cv.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Similarly, concentrations of phenolic compounds were lower in the grasses than the legumes. These findings concur with data reported in the literature for these tropical species (Lee, 2018;Cook et al, 2020;Gaviria-Uribe et al, 2020), where CP values for grasses can range between 40 and 140 g kg −1 DM, and for both legumes studied here, shrub and herbaceous, ranged between 190 and 250 g CP kg −1 DM. However, the CP content obtained in the present study was slightly lower than that reported by Peters et al (2002) for U. brizantha cv.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, the NDF content was within the range of 600 and 800 g kg −1 DM reported for U. brizantha sp. (Cook et al, 2020;Gaviria-Uribe et al, 2020). However, forage quality has been shown to be closely related to pasture age (Vendramini et al, 2014;Gaviria-Uribe et al, 2020) and the time of the year (Demarchi et al, 2016;Abdalla et al, 2019 Geleti et al (2013), while the ME for grasses are above those obtained by Nguku (2015) for 9 grasses of the genus Urochloa, whose values ranged between 6.6 and 5.9 MJ ME kg −1 DM.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations